DIGITAL HERITAGE RECONSTRUCTION TECHNIQUES FOR REVIVING LOST OR DAMAGED VISUAL ART TRADITIONS - Kurulekar, Mahesh; Zhao, Yan; Sahu , Dr. Badri Narayan; Kalidhas , Aravindan Munusamy; Parashar, Komal; C. K., Rajashri; V., Sivasankari (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The further reduction of the environment, natural disasters, and human strife have complicated the preservation of the cultural heritage, particularly visual art traditions, even more. Even though effective, there are times when the traditional methods of restoration are not sufficient even in the restoration of highly damaged or lost works. The reconstruction methods of digital heritage have in their turn responded in the form of new solutions that consider the computer technologies and cultural and historical experience. The paper is a discussion of the different methods of digital reconstruction which are image based, three-dimensional (3D) reconstruction, artificial intelligence based in terms of Generative Adversarial Networks (GANs) and diffusion model-based methods, and also architectures that combine both of these techniques. The research will be based on the mixed-method approach because the qualitative analysis of the cultural and historical context and the quantitative analysis of the methods of calculation will be incorporated into the research. The examples of good and effective application of these means are evidenced by the case studies of ruined paintings, lost murals, and cultural objects. These findings show that single methods have received some benefits but hybrid ones is always accurate, realistic and culturally real. Additionally, the access and engagement of users can be extended through introducing immersive technologies, including augmented reality (AR) and virtual reality (VR), and push the heritage preservation limits. Regardless of these developments, the issues, which are associated with the availability of data, the difficulty of calculations, and moral issues are contemporary. According to the research it is established that the necessity to implement the use of the standardized assessment instruments and interdisciplinary cooperation exists, as there is the necessity to provide that the findings of the reconstruction process should be alike and culturally competent.